2020
DOI: 10.3390/molecules25204684
|View full text |Cite
|
Sign up to set email alerts
|

Kathon Induces Fibrotic Inflammation in Lungs: The First Animal Study Revealing a Causal Relationship between Humidifier Disinfectant Exposure and Eosinophil and Th2-Mediated Fibrosis Induction

Abstract: Currently available toxicity data on humidifier disinfectants are primarily limited to polyhexamethylene guanidine phosphate-induced lung fibrosis. We, therefore, investigated whether the sterilizer component Kathon, which is a mixture of chloromethylisothiazolinone and methylisothiazolinone, induces fibrotic lung injury following direct lung exposure in an animal model. Mice were intratracheally instilled with either the vehicle or Kathon. Differential cell counts, cytokine analysis, and histological analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…34 The actual airborne level of CMIT and MIT formed during animal testing is unknown. Song et al 35 reported that intra-tracheal installation of Kathon containing a mixture of CMIT and MIT induced fibrotic lung injury following direct lung exposure in a mouse animal model, demonstrating that a mixture of CMIT and MIT causes lung fibrosis in the alveoli part of the respiratory tract if it reaches it. In terms of strict causality during the criminal proceedings, the court gave precedence to inhalation animal testing results that did not find lung injury toxicity over the multiple human HDLI victims who used HD products.…”
Section: Resultsmentioning
confidence: 99%
“…34 The actual airborne level of CMIT and MIT formed during animal testing is unknown. Song et al 35 reported that intra-tracheal installation of Kathon containing a mixture of CMIT and MIT induced fibrotic lung injury following direct lung exposure in a mouse animal model, demonstrating that a mixture of CMIT and MIT causes lung fibrosis in the alveoli part of the respiratory tract if it reaches it. In terms of strict causality during the criminal proceedings, the court gave precedence to inhalation animal testing results that did not find lung injury toxicity over the multiple human HDLI victims who used HD products.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight published studies using non-human animal subjects or in vitro toxicology studies were included in the review ( Table 3 ). 16 39 40 41 42 43 44 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 To investigate the hazardous effects of humidifier disinfectants, in vitro studies were performed using various cell lines, and toxicity tests were performed using several animal models. Cytotoxicity, lung fibrosis, and pulmonary genotoxicity due to PHMG exposure were described as a consequence of toxicity testing undertaken shortly after HDLI was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological investigations and medical and biological research have revealed that polyhexamethylene guanidine phosphate (PHMG-p), a main constituent of HD, is highly correlated with inflammatory lung fibrosis. These concomitant lung injuries following respiratory exposure to HDs are known as HD-associated lung injuries (HDLI) [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%